OPTIMUM study protocol: an adaptive randomised controlled trial of a mixed whole-cell/acellular pertussis vaccine schedule. Issue 12 (17th December 2020) - Perez Chacon, Gladymar; Estcourt, Marie J; Totterdell, James; Campbell, Dianne E; Perrett, Kirsten P; Marsh, Julie A; Richmond, Peter C; Wood, Nicholas; Gold, Michael S; Holt, Patrick G; Waddington, Claire S; Snelling, Thomas L
Abstract : Introduction: Combination vaccines containing whole-cell pertussis antigens were phased out from the Australian national immunisation programme between 1997 and 1999 and replaced by the less reactogenic acellular pertussis (aP) antigens. In a large case–control study of Australian children born during the transition period, those with allergist diagnosed IgE-mediated food allergy were less likely to have received whole-cell vaccine in early infancy than matched population controls (OR: 0.77 (95% CI, 0.62 to 0.95)). We hypothesise that a single dose of whole-cell vaccine in early infancy is protective against IgE-mediated food allergy. Methods and analysis: This adaptive double-blind randomised controlled trial is investigating whether a mixed whole-cell/aP vaccine schedule prevents allergic disease in the first year of life. The primary outcome is IgE-mediated food allergy by 12 months of age. Secondary outcomes include new onset of atopic dermatitis by 6 or 12 months of age; sensitisation to at least one allergen by 12 months of age; seroconversion in anti-pertussis toxin IgG titres after vaccination with aP booster at 18 months of age; and solicited systemic and local adverse events following immunisation with pertussis-containing vaccines. Analyses will be performed using a Bayesian group sequential design. Ethics and dissemination: This study has been approved by the Child and Adolescent Health Service Human Research Ethics Committee, Perth, Western Australia (RGS 00019). The investigators will ensure that this trial is conducted in accordance with the principles of the Declaration of Helsinki and with the International Conference on Harmonisation Guidelines for Good Clinical Practice. Individual consent will be requested. Parents will be reimbursed reasonable travel and parking costs to attend the study visits. The dissemination of these research findings will follow the National Health and Medical Research Council of Australia Open Access Policy. Trial registration number: ACTRN12617000065392p.